The value of a statistical life-year in sub-Saharan Africa: evidence from a large population-based survey in Tanzania - Patenaude, Bryan N.; Bärnighausen, Till (Value in health regional issues, 2019)
Background - The value of a statistical life-year (VSLY) is the central number for the economic allocation of health resources. Nevertheless, empirical data on VSLY are lacking for most low- and middle- income countries. In the absence of empirically established VSLY, researchers typically use an arbitrary 3-times multiple of per-capita gross domestic product or per-capita income per life-year saved to establish cost-effectiveness. - Objective - In this study, we establish an empirical VSLY for the first time for a community in sub-Saharan Africa. - Methods - To empirically establish VSLY, we randomly selected 4000 individuals in the Ukonga community of Tanzania and employed a contingent valuation survey to measure VSLY. Using the contingent valuation methodology, we elicited willingness to pay for a 2% mortality risk reduction and had individuals convert this into an annualized payment to be paid each year over their expected remaining life. - Results - We compared our elicited value to per-capita income and found that mean VSLY is $9340 (95% CI $6206-$12 373). The mean annual income in our sample was $2069, resulting in a VSLY that is equivalent to 4.5 times per-capita income. - Conclusion - Our results provide empirical evidence to support moving away from using the World Health Organization cost-effectiveness thresholds in practice because they will likely result in inefficient underinvestment in cost-effective interventions, even in relatively poor samples.
Gesehen am 06.04.2020